ANALISIS PENGARUH FASILITAS WISATA PEMANDANGAN TERHADAP KEPUASAN PENGUNJUNG (Sebuah Kajian Pada Kawasan Danau Toba Kabupaten Simalungun) - Ade Kurnia Harahap, Muhammad (Universitas, 2021)
The service aims to analyze the effect of a tourist destination's facilities on visitor satisfaction (satisfaction) in the Lake Toba area, Simalungun Regency. This research was conducted in several scenic tourist destination spots which the local community called Panatapan in Simalungun Regency, with a total of 313 respondents. Sources of data used are primary and secondary data obtained through questionnaires and documentation. Analysis of the data used in this study using Structural Equation Modeling (SEM) with SmartPLS 3.0 tools. The results showed the importance of developing tourist destination facilities at Kawsan Lake Toba in an effort to increase tourist visitor satisfaction.